The Influence of Investor Psychology on Regret Aversion (Global Journal of Management and Business Research, 2015)
Financial Theories say that Investor should act rationally. Emotions do have a powerful impact on everyday decisions we make. They not only shape behavior but also affect every decision taken by an individual. Similarly regret is the most common phenomena observed in individuals especially when they take investing decisions. In the present study researchers have tried to find out influence of Investor Psychology on Regret Aversion by using General Linear Model. The results are useful in Indian context.
Keywords: regret aversion; risk; investor psychology